Prevalence of neoplasia in solitary and multiple esophago-gastrointestinal polyps: 5 years retrospective histopathological study - Mehdi, Ahmed Hamdi (Cellular and Molecular Biology, 2021)
The increasing use of endoscopy has led to more discernable abnormalities in the stomach, including polyps. Gastric polyps encompass a spectrum of pathologic conditions that can vary in histology, neoplastic potential, and management. Despite their high prevalence, there is a paucity of literature to support management and treatment decisions for endoscopists. The goal of this review is to summarize clinical, endoscopic, and histopathologic features of various polyps, review syndromes associated with such polyps and provide management recommendations. The present study was carried out for analyzing and comparing the prevalence of neoplasia in polyps (Solitary and multiple) removed endoscopically from the esophagus, stomach, and bowel undergoing screening. Five years retrospective study was done on patients who underwent endoscopy procedures including Oesophagogastroduodenoscopy (OGD) and colonoscopy between June 2015 and March 2019 in Faruk Medical City Hospital, Sulaimani City. Age and sex of patients, site of occurrence, number of polyps (solitary or multiple), and polyps' histologic type of 369 cases were analyzed in this study. Regarding solitary polyps, out of 279 polyps, 155 were neoplastic (55%) and 124 were non-neoplastic polyps, while multiple polyps, out of a total of 90 cases, 68 were neoplastic (75%) and 22 were non-neoplastic. More than 78% of patients were above the age of 40 years. Tubular adenoma was the most commonly diagnosed polyp. Large bowel was the most commonly involved site and left-sided polyps outnumbered right-sided ones with the sigmoid colon being the most commonly involved site. Screening programs including endoscopy, especially the colon for detecting polyps and particularly the colorectal region can be helpful to reduce morbidity and mortality of patients.